Micro-macroscopic modeling of a lithium-ion battery by considering grain boundaries of active materials. (10th October 2021) - Sarkar, Susmita; Hoffmann, John Alexander; Park, Jonghyun
Abstract: Many important properties of electrode materials are profoundly sensitive to deviations from the crystalline perfection. Among them are grain boundaries, which play an important role on battery performance by altering the distributions of ions inside the particles and changing the corresponding stress level. This paper explores the mechanical and microstructural aspects of battery behavior by developing a cell-level model that incorporates grain boundary diffusion in the electrode particles for the anode and cathode. The developed model is compared against a grainless model at various operating conditions to understand how grain boundaries influence capacity and stress generation. The results from the model revealed that the location of the maximum stress might not necessarily occur at the separator interface at any given time as the particles with heterogeneous diffusion paths displayed gradual changes in flux profile, which has just been believed in practice. The grain structure geometry variability showed that less diffusive particles at the rear side endure more stress than high diffusive frontal particles. Also, the results show an appreciable effect of grain boundary diffusion on the voltage profile of the cell for the tested parameters and, overall, a significant reduction in the maximum induced stress in the cell. Stress behavior between the anode and cathode differ significantly and show that the effective diffusivity of a particle might matter much more significantly than its location in the cell. With heterogeneous particle shape modeling capabilities, this approach can be next-generation battery model that improves understanding of battery materials and electrodes. Graphical abstract: Image, graphical abstract